Participatory Development Communication in Mitigating Forest and Land Fires in Riau Province - Miftah Faridl Widhagdha; Wahyu Purwanto; Rahmad Hidayat (Department of Communications, Universitas Islam Indonesia, 2019)
This study examines CSR programs for mitigating forest and land fires in Riau Province carried out by the private sector, namely PT Pertamina Refinery Unit II Sungai Pakning through a participatory development communication approach. This research was conducted in the community assisted by CSR of PT Pertamina (Persero) Refinery Unit II Sungai Pakning located in Sungai Pakning Village, Bukit Batu District, Bengkalis Regency, Riau Province. This research method uses qualitative methods by collecting data through participant observation. The results of this study indicate that the participatory development communication approach carried out by PT Pertamina (Persero) Refinery Unit II Sungai Pakning CSR in carrying out forest and land fire mitigation activities is carried out through four stages of participatory communication namely heteroglosia, polyphony, dialogue and carnival. These four stages of participatory communication are supported because of the still close communitarian tradition and the enactment of deliberative communication in the decision-making process at the local level. In this study it was also found that the role of local leaders as opinion leaders was still needed in conveying important information. The role of local leaders is not merely an informal symbol, but also an influential party in determining the diversity of the community, mediators in public discussions and dialogues, and guards of local customs that are still held by the community. Therefore, the participatory communication approach based on the four characters mentioned earlier is important to involve the role of local leaders so that the messages communicated can be more optimal. Keywords: CSR, Development Communication, Participatory Communication